2013
DOI: 10.1089/vbz.2012.1073
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Catarina Virus (familyArenaviridae) in Southern Texas, 2001–2004

Abstract: A total of 3941 rodents were captured during a 46-month prospective (mark-recapture) study on the ecology of Catarina virus in southern Texas. Antibody reactive against Catarina virus was found in 73 (11.9%) of 611 southern plains woodrats (Neotoma micropus) and none of 3330 other rodents; strains of Catarina virus were isolated from 6 antibody-negative and 9 antibody-positive southern plains woodrats; and the infections in at least 3 southern plains woodrats were chronic. These results affirm the notion that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Previously, arenavirus AV 98490013 was isolated from a southern plains woodrat captured at BMSP (Cajimat et al 2011); anti-arenavirus antibody was found in southern plains woodrat TK77260, 5 (5.8%) of 86 other rodents captured at FBMB, and 16 (4.1%) of 390 rodents captured at FLOM, AFTN, and MSSP (Table 1); arenavirus AV H0380005 was isolated from woodrat TK77260 (Cajimat et al 2011); and the 6 CTNV strains in this study (Table 2) were isolated from southern plains woodrats captured at the CWMA in 1999--2004 (Fulhorst et al 2002, Milazzo et al 2013). In this study, fresh-frozen samples of kidney and spleen from the rodents captured at FBMB, FLOM, AFTN, and MSSP were acquired from the Museum of Texas Tech University and tested for arenavirus.…”
Section: Methodsmentioning
confidence: 58%
See 2 more Smart Citations
“…Previously, arenavirus AV 98490013 was isolated from a southern plains woodrat captured at BMSP (Cajimat et al 2011); anti-arenavirus antibody was found in southern plains woodrat TK77260, 5 (5.8%) of 86 other rodents captured at FBMB, and 16 (4.1%) of 390 rodents captured at FLOM, AFTN, and MSSP (Table 1); arenavirus AV H0380005 was isolated from woodrat TK77260 (Cajimat et al 2011); and the 6 CTNV strains in this study (Table 2) were isolated from southern plains woodrats captured at the CWMA in 1999--2004 (Fulhorst et al 2002, Milazzo et al 2013). In this study, fresh-frozen samples of kidney and spleen from the rodents captured at FBMB, FLOM, AFTN, and MSSP were acquired from the Museum of Texas Tech University and tested for arenavirus.…”
Section: Methodsmentioning
confidence: 58%
“…Previous studies revealed a high level of diversity among the nucleotide sequences of the N protein genes of CTNV strains associated with N. micropus on the CWMA (Fulhorst et al 2002, Milazzo et al 2013) and a high level of genetic diversity in N. micropus on the CWMA (Méndez-Harclerode et al 2007). This study revealed a similar level of diversity among the nucleotide sequences of the N protein genes of arenaviruses associated with N. micropus on FBMB, and even higher levels of diversity among the nucleotide sequences of the GPC genes of arenaviruses associated with N. micropus on the CWMA and among the nucleotide sequences of the GPC genes of arenaviruses associated with N. micropus on FBMB (Table 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin nombre virus (hantavirus) has been identified in four species of Neotoma from Arizona and Utah (Dearing et al, 1998). in North America (Kosoy et al, 1996;Lele et al, 2003;Milazzo et al, 2013). One or more indigenous arenaviruses are associated with Neotoma spp.…”
Section: Use In Researchmentioning
confidence: 99%
“…Other Bunyaviridae (Jamestown Canyon virus and Morro Bay virus) were isolated from the dusky-footed wood rat in California . Some, like Catarina virus, are only believed to affect wood rats (Milazzo et al, 2013). in North America (Kosoy et al, 1996;Lele et al, 2003;Milazzo et al, 2013).…”
Section: Use In Researchmentioning
confidence: 99%